Human Capital Versus Sorting: The Effects of Compulsory Attendance Laws - Lang, Kevin; Kropp, David (Quarterly Journal of Economics, 1986)
Under the educational sorting hypothesis a state compulsory school attendance law will increase the educational attainment of high-ability workers who are not directly affected by the law. Under the human capital hypothesis such laws affect only those individuals whose behavior is directly constrained. We find that compulsory attendance laws do increase enrollment rates in age groups they do not affect directly. Thus, our results contradict the human capital hypothesis and are consistent with the sorting hypothesis.